2013
DOI: 10.1108/15587891311300990
|View full text |Cite
|
Sign up to set email alerts
|

Economic reforms, determinants and stability of dividends in a dynamic setting

Abstract: Purpose -This study aims to find whether the Indian private corporate sector follow stable cash dividend policies, whether dividends smoothen earnings, estimate the implicit target dividend ratio, and examine the determinants along with speed of adjustment of dividends towards a long run target ratio.Design/methodology/approach -The study uses the instrumental variable (IV) approach for dynamic panel data for 1971-2010 periods controlling for economic reforms. The GMM-in-levels model, GMM-in-first-differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 82 publications
1
2
0
Order By: Relevance
“…The sector-wise panel regression in Appendix A reveals a strong positive relation between the tangibility of assets (TANG) and the dividend policy for firms from the AGRO, MINING, ENGG, TEXTILE, CONSGDS, CONSTR, and LOGIS sectors. This implies that the companies in these sectors tend to pay dividends if they have higher TANG, in line with past studies e.g., (Aivazian et al 2003a;DeAngelo et al 2004;Denis and Osobov 2008;Subhash Kamat and Kamat 2013). However, TANG has an inverse relation with dividend policy for firms of the BANKING-sector.…”
Section: Operating Measuressupporting
confidence: 86%
See 1 more Smart Citation
“…The sector-wise panel regression in Appendix A reveals a strong positive relation between the tangibility of assets (TANG) and the dividend policy for firms from the AGRO, MINING, ENGG, TEXTILE, CONSGDS, CONSTR, and LOGIS sectors. This implies that the companies in these sectors tend to pay dividends if they have higher TANG, in line with past studies e.g., (Aivazian et al 2003a;DeAngelo et al 2004;Denis and Osobov 2008;Subhash Kamat and Kamat 2013). However, TANG has an inverse relation with dividend policy for firms of the BANKING-sector.…”
Section: Operating Measuressupporting
confidence: 86%
“…Reddy and Rath (2005) have reported that more profitable companies, having lesser opportunities to invest with a larger size, are likely to distribute dividends in India. Subhash Kamat and Kamat (2013) have reported that for Indian companies, the tangibility of assets, size, and earnings are significant for determining payout policies. The results are consistent with (Fama and French 2001;DeAngelo et al 2004;Denis and Osobov 2008).…”
Section: Factors Affecting Dividend Policymentioning
confidence: 99%
“…Profitability (either measured using ROE or return on assets) has been found to be positively associated with dividends (Abor and Bokpin, 2010; Aivazian et al , 2003; Al-Najjar and Kilincarslan, 2017; Amidu and Abor, 2006; Baker et al , 2007; Baker et al , 2013; Benito and Young, 2003; Bhat and Pandey, 1994; Bhattacharya, 1979; Goergen et al , 2005; DeAngelo et al , 2004; Denis and Osobov, 2008; Easterbrook, 1984; Fama and French, 2001; Ferris et al , 2006; Ho, 2003; Jensen et al , 1992; Li and Lie, 2006; Mahapatra and Sahu, 1993; Mishra and Narender, 1996; Mitton, 2004; Mohamed et al , 2012; Reddy and Rath, 2005; Renneboog and Trojanowski, 2007; Subhash Kamat and Kamat, 2013; von Eije and Megginson, 2008; Yarram, 2015; Yusof and Ismail, 2016). The findings for both the static and dynamic panel data models show that profitability (ROE) less the COE, referred to as ER (used to measure shareholder value), is positively associated with dividends.…”
Section: Discussionmentioning
confidence: 99%